MiR-122-5p Mitigates Inflammation, Reactive Oxygen Species and SH-SY5Y Apoptosis by Targeting CPEB1 After Spinal Cord Injury Via the PI3K/AKT Signaling Pathway - Wei, Zijian; Liu, Jun; Xie, Hao; Wang, Binbin; Wu, Ji; Zhu, Zezhang (Neurochemical research, 2021)
Spinal cord injury (SCI) is a threatening disease that lead to severe motor and sensory deficits. Previous research has revealed that miRNAs are involved in the pathogenesis of a variety of diseases. However, whether miR-122-5p was involved in SCI was rarely investigated. In our study, we intended to probe role of miR-122-5p in the regulation of inflammatory response, reactive oxygen species (ROS) and SH-SY5Y apoptosis. We found miR-122-5p was downregulated in SCI mouse model and LPS-induced SH-SY5Y cells. Moreover, miR-122-5p overexpression alleviated inflammatory response, ROS and SH-SY5Y apoptosis in SCI mice. In addition, miR-122-5p elevation also mitigated SCI in LPS-induced SH-SY5Y cells. Additionally, cytoplasmic polyadenylation element binding protein 1 (CPEB1) was verified to be a target of miR-122-5p. CPEB1 expression was upregulated in SCI mouse model and LPS-induced SH-SY5Y cells. CPEB1 expression was negatively related to miR-122-5p expression. Moreover, CPEB1 activated the PI3K/AKT signaling pathway in SH-SY5Y cells. Finally, CPEB1 elevation recovered the suppressive effect on inflammatory response, ROS and SH-SY5Y apoptosis in LPS-treated SH-SY5Y cells mediated by miR-122-5p upregulation and through the PI3K/AKT signaling pathway.